Revision of the Oriental species of Calleida Latreille (sensu lato). Part 1: Introduction, groups of species, and species of six species groups (Coleoptera: Carabidae: Lebiini) - Casale, Achille; Shi, Hongliang (Zootaxa, 2018)
This revision focuses on the genus Calleida Latreille, 1824 (in the widest sense) in the Oriental Region, previously treated as genus or subgenus Callidiola Jeannel, 1949. In the present contribution, as first part of a series of revisions of the Asiatic Calleida species, we define nine species groups including all known Asiatic species, based on external features and morphological characters of male and female genitalia. A key for the identification of all nine species groups is provided, along with diagnostic characters, included species, geographical distribution, and brief discussion on monophyly and relationships for each species group. In particular, the present contribution deals with species of six small species groups, including eleven species in total, for which keys to all known species, descriptions, distribution maps, habitus images and genitalia illustrations are provided.Five new species are described: Calleida gressittiana Casale & Shi, sp. n. (type locality: Kinabalu, Sabah, Borneo), Calleida puncticollis Shi & Casale, sp. n. (type locality: Zigui, Hubei), Calleida jelineki Casale & Shi, sp. n. (type locality: Coimbatore, India), Calleida viet Casale & Shi, sp. n. (type locality: Vung Tau, Vietnam), Calleida borneensis Shi & Casale, sp. n. (type locality: Sabah, Borneo). Lectotypes for five taxa are designated. One synonymy is newly proposed: Calleida lieftincki Louwerens junior synonym of Calleida corporaali Andrewes, syn. nov.